2019
DOI: 10.3390/cancers11081124
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Visual Acuity Deterioration and Radiation-Induced Toxicities after Brachytherapy for Choroidal Melanomas

Abstract: Ruthenium-106 (Ru-106) brachytherapy is an established modality for eye-preserving treatment of choroidal melanoma. To achieve optimal treatment outcomes, there should be a balance between tumour control and the risk of healthy tissue toxicity. In this retrospective study, we examined normal tissue complication probability (NTCP) for visual acuity deterioration and late complications to aid the understanding of dose-dependence after Ru-106 treatments. We considered consecutive patients diagnosed with choroidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Importantly, these data cannot be compared directly with the hypofractionated physical doses used for choroidal melanomas. Similarly, the current results will not be applicable to brachytherapy with ruthenium 106 31 because of the different dose-fractionation and dose-rate effects and different underlying radiobiology of the radiation methods.…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, these data cannot be compared directly with the hypofractionated physical doses used for choroidal melanomas. Similarly, the current results will not be applicable to brachytherapy with ruthenium 106 31 because of the different dose-fractionation and dose-rate effects and different underlying radiobiology of the radiation methods.…”
Section: Discussionmentioning
confidence: 90%
“…A dosimetric advantage of kilovoltage application on this kind of tissue surface is also remarkable, due to its sharp fall-off dose profile compared to photon- or electron-based teletherapy units [ 21 , 22 ]. This feature allows better OAR sparing, as historical data report elevated rates of cataract, higher-grade conjunctivitis, uveitis and ulcer, amongst others [ 42 , 43 , 44 ]. Newly published data suggested that proton therapy might also be an optimal EBRT option.…”
Section: Discussionmentioning
confidence: 99%
“…Barker also suggested that the brachytherapy-planning protocols used for 125 I, for example COMS, were not sufficient for 106 Ru plaque brachytherapy due to the dosimetric difference between 125 I und 106 Ru. Three large 106 Ru treatment series with a mean dose of 100 Gy to the apex reported 5-year local control rates at 78, 82, and 84% respectively [19][20][21]. Another prospective study of 106 Ru brachytherapy on 450 patients reported that a 5-year local control rate of 97.9% could be achieved if a minimalscleral radiation dose of 300-400 Gy was used [22].…”
Section: Discussionmentioning
confidence: 99%